Faktor–Faktor yang Mempengaruhi Tingkat Pendapatan Pedagang Ikan di PPI Bonehalang Kelurahan Benteng Selatan Kabupaten Kepulauan Selayar - Latif, Abdul; Azzahra, Fatimah; Arafat, Yasser; Mustafa, Mustafa; Awaluddin (FISHIANA Journal of Marine and Fisheries, 2024)
This research aims to determine the factors that influence the income level of fish traders at PPI Bonehalang, including age, length of business, level of education, and number of dependents. This research is a type of qualitative research using primary data, primary data was obtained from questions given to fish traders as many as 30 respondents using a questionnaire. The results of the research show that there is an influence of age, education, and number of dependents on the income level of fish traders at PPI Bonehalang.